2012
DOI: 10.4315/0362-028x.jfp-11-505
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Salmonella and Listeria monocytogenes in Delicatessen Salads and Hummus as Affected by Sodium Content and Storage Temperature

Abstract: A study was conducted to determine survival and growth behavior of Salmonella and Listeria monocytogenes in commercially prepared mayonnaise-based potato salad, macaroni salad, and coleslaw and in hummus (initial mean pH values were 4.80 to 4.94, 4.18 to 4.31, 3.87, and 4.50 to 4.52, respectively) as affected by sodium concentration (133 to 364, 190 to 336, 146 to 272, and 264 to 728 mg/100 g, respectively) and storage at 4 or 10°C for up to 27 days. Salmonella did not grow in any of the test products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Alali et al (2012) reported that background microflora numbers in salads and dips immediately after preparation were in the range of 2-3 log 10 CFU/g. Similarly, Omar et al (2012) reported APC and YM numbers of eggplant dip samples prepared in the laboratory to be 3 and 2.5 log 10 CFU/g, respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Alali et al (2012) reported that background microflora numbers in salads and dips immediately after preparation were in the range of 2-3 log 10 CFU/g. Similarly, Omar et al (2012) reported APC and YM numbers of eggplant dip samples prepared in the laboratory to be 3 and 2.5 log 10 CFU/g, respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…After 7 d storage at this temperature, the pH values decreased in samples with 0, 0.4, 0.6 and 0.8% citric acid from 5.respectively. Previous studies on the effects of storage temperature and pH on the survival and growth of foodborne pathogens in salad/dip such as non-tahini-based eggplant salad and tahini-based products such as hummus dip (cooked, mashed chickpeas blended with tahini, lemon juice, garlic and salt) were found in the literature(Skandamis and Nychas, 2000;Tassou et al, 2009;Al-Holy et al 2006;Alali et al 2012). These studies also found that the survival and growth of foodborne pathogens in these products depended on intrinsic (e.g.…”
mentioning
confidence: 92%
“…typhimurium growth was observed in the temperature range of 25–37 °C at pH 4.5 [48,49]. Alali et al [50] proposed that lowering the pH of the mayonnaise-based homemade salads decreased the rate of survival of Salmonella regardless of the temperature. According to a study conducted by Koutsoumanis et al [51], the minimum pH value that permitted the growth of S. typhimurium was 3.94 within the temperature range 25–35 °C.…”
Section: Ph/acid Tolerance and Temperaturementioning
confidence: 99%
“…Viability of Salmonella decreased as the amounts of vinegar and lemon juice in mayonnaise increased.[35]France S . typhimurium Reduced-calorie mayonnaisepH/TemperatureHigher temperature with a low pH, greater the inactivation of the organism.[78]U.S. Salmonella Mayonnaise-based potato salad, macaroni salad, and coleslawpH, NaCl, and temperatureDecreased pH and increased the bactericidal activity irrespective of sodium concentration or storage temperature Sodium concentrations had little or no effect on the behavior of Salmonella when stored at 4 or 10 °C for up to 27 days.[50]U.K. S. EnteritidisMayonnaisepH acetic acid (vinegar)Mayonnaise made with vinegar to a pH of 4.1 or less controlled S. Enteritidis. Storage of mayonnaise at refrigeration temperatures protected Salmonella spp.…”
Section: Table A1mentioning
confidence: 99%
“…Therefore, a lower salad pH may be needed to prevent the growth of L. monocytogenes in mayonnaise-based salads. For example, Alali et al (2012) reported that L. monocytogenes was not able to grow in commercially prepared mayonnaise-based potato salads of pHs 4.8-4.9, macaroni salads of pHs 4.2-4.9 and coleslaw of pH 4.5. Comparing the results (Table 1) with other studies reporting the growth of L. monocytogenes in cultural media under conditions similar to those found in mayonnaisebased salads, the present study showed that L. monocytogenes was more readily to grow in ham salads.…”
Section: Growth Of L Monocytogenes In Ham Saladsmentioning
confidence: 99%